Ethnic inclusion, education, durable assets and occupational opportunities - Aboud, Nihad (AUC Knowledge Fountain, 2016)
The purpose of this study is to examine the effect of access to durable economic assets,education and occupational opportunities on political inclusion. The study uses aggregated cross sectional data from the DHS surveys and combines it with data from the EPR dataset to obtain measures of economic, social and political inequalities at the group level. The study assumes that the more economic deprivation would lead to reduced political inclusion, whereas increased share of access to education and modern occupations increase the likelihood of political inclusion. The main findings of the study suggest a negative relation between relative economic deprivation and moderns occupation (clerical…)on political inclusion, whereas a positive relation between education and political inclusion.